DAMPAK EKSTERNALITAS PEMBANGUNAN JALAN EXIT TOL PEKALONGAN- BATANG TERHADAP KONDISI EKONOMI MASYARAKAT SEKITAR (PASAR GROSIRSETONO) (Sahmiyya: Jurnal Ekonomi dan Bisnis, 2022)
The construction of the Pekalongan-Batang Exit Toll Road provides a positive externality for the surrounding community, one of which is the Setono wholesale batik market traders. Toll road construction which was originally a toll road Trans Java does not pass through the City area Pekalongan and the toll exits that were built are Batang Regency. City government Pekalongan strives for operationalization Trans Java toll road does not close access Pekalongan City area. The Setono wholesale market is getting busier and more visitors from inside and outside the city see and buy batik products which are part of Indonesia’s cultural heritage. In this development, land community settlements that are used as locations for road construction the toll road causes residents to have to move to find a new location. And as the community’s need for land increases because with the construction of toll roads, making agricultural lands now make it an alternative way to meet the need for land. The existence of the toll road provides positive externalities for wholesale batik sellers in Setono, including being an alternative road that can always be used in private and public transportation so that it is more efficient in the travel time is so fast it also reduces congestion, the price selling land around the toll exit road increased dramatically, and the wholesale market was getting busier and morepopular, etc. Research data will be collected through observation and interviews which will then be processed using descriptive analysis methods.